Optimalisasi Tindak Lanjut Laporan Hasil Pemeriksaan di Kementerian Pertanian: Peran Pimpinan dan Tim TLHP - Dewi Safriani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze the response of work units (satker) to the follow-up of Audit Reports (LHP) at the Ministry of Agriculture. Audit Reports issued by oversight institutions, such as the Inspectorate General, act as a stimulus to identify issues and provide recommendations that need to be addressed by the work units. The response is influenced by the readiness, commitment, and capabilities of leaders and staff responsible for the follow-up process. The study found that leadership commitment is crucial in determining the effectiveness of the follow-up; leaders who do not emphasize the importance of Audit Report Follow-Up (TLHP) tend to weaken the organizational drive to act. As a solution, work units that optimally follow up on audit findings establish organized TLHP teams, formulate clear action plans, and conduct regular monitoring and evaluation. This ensures that all recommendations are followed up on time and in accordance with procedures.